Shine on me: Industry coherence and policy support for emerging industries - Georgallis, Panayiotis (Panikos); Dowell, Glen; Durand, Rodolphe (Administrative Science Quarterly)
Although the emergence of new industries is often attributed to state support, little is known about the conditions under which an emergent category of organizations comes to receive state support in the first place. We theorize how government support for a nascent industry is jointly determined by the industry$1 (Bs internal features and external forces and test our arguments by analyzing feed-in tariff policies for the emergent solar photovoltaics (PV) industry in 28 European countries from 1987 to 2012. We find that feed-in tariffs$1 (Bpolicies that incentivize renewable energy$1 (Bwere more likely in countries with greater numbers of solar PV producers and where the industry was more coherent, containing fewer producers coming from industries with a contrasting identity, such as fossil fuels. Further, we find that the concentration of the incumbent (rival) energy sector in a given country enhances the effect of the number of PV producers on government policy support, but only when the emerging industry has a coherent identity. Our results shed new light on the relationship between public policy and the emergence of an industry category, and they extend our understanding of how new industries can attain valuable state support while operating in seemingly hostile environments. - Reproduced.s
Keywords: Institutionalisation